TRADISI BAJARAHAN MASYARAKAT BANJAR SAAT IDUL FITRI DI MASA PANDEMI COVID-19 “STUDI KASUS KOTA BANJARMASIN” - Rofiqa Zulfa Salsabila (UIN ANTASARI BANJARMASIN, 2021)
The entry of the Covid-19 pandemic makes bajarahan traditions that have been implemented for decades for generations by the banjar community difficult to implement because of several government policies such as lockdown, crowd restrictions, and PPKM. The purpose of this research is to find a solution, so that the Bajarahan tradition of banjar people can still be carried out in the pandemic period. This research uses methods of literature studies with a qualitative descriptive approach. The data collection was conducted through in-depth interviews with three participants from pekapuran B Laut residents. The results of this article show that the Bajarahan tradition can still be implemented during the pandemic with a solution, namely the pandemic by applying physical distancing, health protocols, restrictions on people and the region of the implementation of bajarahan traditions, as well as wrapped dishes to take home.